Model pendidikan olahraga (SEM) tentang motivasi dan aktivitas fisik siswa di kelas: Tinjauan pustaka - Schiff, Nancy Trisari; Supriady, Andy (Universitas Nusantara PGRI Kediri, 2023)
Siedentop developed the Sports Education Model (SEM) to provide students with sports knowledge. As research on SEM has continued, attention has focused on (a) student motivation and (b) opportunities for physical activity in physical education classes. This study contains a literature review related to the Sport Education Model (SEM) on motivation and physical activity to provide evidence to support the idea that this model can achieve physical education learning. This study used 20 journals from 6 databases, namely Google Scholar, Sage Journal, Taylor & Francis, ScienceDirect, ResearchGate, and Academia.edu, with further analysis using synthesis techniques. The research aimed to pursue sports education (SEM) of student motivation and physical activity in physical education classes. This study is an updated review of how implementing the Sport Education Model (SEM) can build students' physical activity motivation and engagement in physical education classes, including the latest research trends for future research.